A critical analysis of the interpretation of the term "associated enterprise" in provisions in South African double taxation agreement based on Article 9 of the Organisation for Economic Cooperation and Development's Model Tax Convention on Income and on Capital - Greeff, Andre (Stellenbosch : Stellenbosch University, 2020)
Thesis (LLM)--Stellenbosch University, 2020.